2019
DOI: 10.1007/s11837-019-03359-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Corrosion Properties of Two Precipitation-Hardened Mg-Y-Nd-Gd-Dy Alloys with Small Changes in Chemical Composition

Abstract: Nd alloys is based on finely dispersed particles an effective strengthening mechanism to achieve high strength at moderate ductility. However, these particles often affect corrosion by being more noble than the matrix. Biodegradable implant materials should show a corrosion rate fit to its application but should be free of pitting corrosion. Especially deep and narrow pits act as notches and cause increased mechanical stress leading into early failure. WE43 has already shown to have an acceptable biological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Because with a lower corrosion rate as a result of passivation (see Fig. 8) the pitting factor increases when the oxide layer is obviously not dense enough, which agrees with the immersion tests [54]. However, pitting factor is the lowest in the as-cast Q5 alloy.…”
Section: Resultssupporting
confidence: 80%
“…Because with a lower corrosion rate as a result of passivation (see Fig. 8) the pitting factor increases when the oxide layer is obviously not dense enough, which agrees with the immersion tests [54]. However, pitting factor is the lowest in the as-cast Q5 alloy.…”
Section: Resultssupporting
confidence: 80%
“…WE43 is a high-strength alloy with an acceptable biological response. [6][7][8] The alloying, manufacturing route and post-heat treatment influence the mechanical and corrosion properties of this material. Nd, for example, is known to form stable intermetallic phases at grain boundaries, as Nd has a low solid solubility in Mg and is therefore added to provide precipitation strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 30 ] reported that the yielding plateau at the initial stage of plastic deformation is mainly ascribed to the activation of, and rapid increase in, basal dislocations. Figure 3 b presents the mechanical properties of different extruded WE alloys [ 14 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], suggesting the overall superior properties of the alloy in this work.…”
Section: Resultsmentioning
confidence: 84%
“… Mechanical properties of the extruded alloy at room temperature. ( a ) Engineering stress–strain curve; ( b ) comparison of the elongation and yield stress of different extruded WE alloys [ 14 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. …”
Section: Figurementioning
confidence: 99%